Between God, the Dead and the Wild Chamba Interpretations of Ritual & Religion - Fardon, Richard (Edinburgh University Press, 2022)
Based on observations in two West African villages - one a traditionally uncentralised community in contemporary Nigeria, the other a small chiefdom in Cameroon - this study shows that despite basic presuppositions regarding various types of being, the beliefs of the two groups manifest themselves in quite different ways. Focusing particularly on Chamba conceptions of people, masks and cults, Richard Fardon applies contemporary social theory to Chamba religion and shows how particular individuals integrate their concerns with notions of human purpose, the agricultural cycle and the values of the wilds
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mrz 2022)
Keywords: African Studies; SOCIAL SCIENCE / Anthropology / Cultural & Social